If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18(0) + 9y = -43 Multiply -18 * 0 0 + 9y = -43 Anything times zero is zero. 0 + 9y = -43 Remove the zero: 9y = -43 Solving 9y = -43 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '9'. y = -4.777777778 Simplifying y = -4.777777778
| 2/3m-1/3=4 | | 1/3+4 | | -2x+3y-12=0 | | 2/3a+b=7 | | -4x^2+360x-80x-4000=0 | | -4x^2+240x+14400=18400 | | 4/9*2=80 | | (12p+14q)and(11p-12q)= | | 3/4x+5/4=50 | | 8=-11+y | | (10x-3)= | | 7=-16+r | | 2(1-x)=3(1+2x)+37 | | -20+x=18 | | 3x-4+1=-2x-5+5 | | n-14=23 | | 19+n=30 | | x-4=14x+9 | | 4/7(2c+9)=3/7 | | 8-3x=12+x | | 6(100-x)+3(100-y)=1500 | | 4x-2+x=-2x+2x | | 2/3x+6=-8 | | 3/5(h+10)=9 | | 4(k+3)+5k=75 | | x/12=16/24 | | x^3+x^2+4=0 | | 3/4x-3=18 | | 3/4-3=18 | | f(x)=28x^2+9x-4 | | 2/3(6t+12)=28 | | X+3/2x+6=0.5 |